2014
DOI: 10.3390/rs6032408
|View full text |Cite
|
Sign up to set email alerts
|

Local Vegetation Trends in the Sahel of Mali and Senegal Using Long Time Series FAPAR Satellite Products and Field Measurement (1982–2010)

Abstract: Local vegetation trends in the Sahel of Mali and Senegal from Geoland Version 1 (GEOV1) (5 km) and the third generation Global Inventory Modeling and Mapping Studies (GIMMS3g) (8 km) Fraction of Absorbed Photosynthetically Active Radiation (FAPAR) time series are studied over 29 years. For validation and interpretation of observed greenness trends, two methods are applied: (1) a qualitative approach using in-depth knowledge of the study areas and (2) a quantitative approach by time series of biomass observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 45 publications
3
61
0
1
Order By: Relevance
“…Herrmann and Tappan (2013) found a reduction of woody species richness and a shift to more xeric species since the early 1980s, as well as an increasing dominance of shrubs in central Senegal. Other studies from Senegal and Mali confirmed these results (Maranz, 2009;Miehe et al, 2010;Herrmann and Tappan, 2013;Brandt et al, 2014bBrandt et al, , 2015Brandt et al, , 2016aSpiekermann et al, 2015). Kaptué et al (2015) refer to a post-drought tree population recovery and present evidence of a decline in populations of economically and culturally important trees and shrubs despite the increase in woody cover.…”
Section: Contributions Of Other Authorssupporting
confidence: 77%
“…Herrmann and Tappan (2013) found a reduction of woody species richness and a shift to more xeric species since the early 1980s, as well as an increasing dominance of shrubs in central Senegal. Other studies from Senegal and Mali confirmed these results (Maranz, 2009;Miehe et al, 2010;Herrmann and Tappan, 2013;Brandt et al, 2014bBrandt et al, , 2015Brandt et al, , 2016aSpiekermann et al, 2015). Kaptué et al (2015) refer to a post-drought tree population recovery and present evidence of a decline in populations of economically and culturally important trees and shrubs despite the increase in woody cover.…”
Section: Contributions Of Other Authorssupporting
confidence: 77%
“…It is directly linked to photosynthesis and therefore expresses a canopy's energy-absorption capacity [21]. Many authors have studied the relationship between FAPAR and NDVI [7,[22][23][24][25][26][27], which has been shown to be generally linear for green vegetation, particularly in the semi-arid environment of the Sahel [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The lower values obtained for Fakara were attributed to a mixed agro-pastoral land use pattern, when compared to the predominantly pastoral land use identified at the Gourma site [126]. The issue of localised land use/cover patterns resulting in mixed pixels was also noted by Brandt et al [127]. This was partially rectified by utilising a higher-resolution NDVI product (Geoland V1 at 5 km resolution), which revealed patterns obscured by the GIMMS3g data.…”
Section: Can Ndvi Trends Capture a Reduction In Npp?mentioning
confidence: 95%